The Antigangrene Activity of Transdermal Patch of Insulin Leaves (Smallanthus Sonchifolius) to Diabetic Gangrene on White Rats: Aktivitas Antigangren Patch Transdermal Daun Insulin (Smallanthus sonchifolius) terhadap Gangrene Diabetik pada Tikus Putih - Lucia Hendriati; Fecky Fernando Fredericktho; Iwan Sahrial Hamid; Teguh Widodo; Suryo Kuncorojakti (Universitas Tadulako, 2023)
Background: Diabetic gangrene is a chronic complication of diabetes mellitus caused by neuropathy, blood vessel disorders, and infection by Staphylococcus aureus. S.sonchifolius leaves contains flavonoid as hypoglycemic agents and sesquiterpene lactones as antibacterial. Unfortunately, oral administration of S. sonchifolius leaves infusion causes kidney toxicity. Objective: The aimed of the study was to determine the effectiveness of the transdermal patch of S. sonchifolius leaves ethanol extract on gangrene wound healing with macroscopic parameters and neoangiogenesis of gangrenous wounds in white rats that have been induced by diabetes mellitus. Material and Methods: This study used 4 treatment groups: positive control (Bevalex® cream), negative control (patch without S. sonchifolius leaves extract), F1 (S. sonchifolius leaves patch without enhancer), and F2 (S. sonchifolius leaves patch with Tween 60 as enhancer). The dose of S. sonchifolius leaves given was 400 mg/kg BW. Alloxan-induced diabetic rat feet were injected with S. aureus to form gangrene. Observations were made on the 7th and 14th days. Results: Based on the Wagner-Meggit scale on macroscopic observations, administration of a transdermal patch of S. sonchifolius leaves accelerates gangrene healing. The statistical results of neoangiogenesis on the 7th and 14th days showed a significant difference (p<0.05) between the positive control, F1, and F2 to the negative control. F2 showed the highest angiogenesis on day 7 (114.00 ± 5,00) and 14 (161.00 ± 5.29) compared to all groups. Tween 60 as enhancer increase the number of angiogenesis. Both F1 and F2 did not show a significant difference to the positive control. Conclusion: S. sonchifolius leaves ethanol extract patch accelerated the diabetic gangrene healing process based on macroscopic and neoangiogenesis observation on the 7th and 14th days. Toxicity examination in white rats are needed before clinical study in human.